PENGARUH PENAMBAHAN JUMLAH BERAT BATU ZEOLIT YANG BERBEDA PADA TRANSPORTASI BENIH IKAN NILA (OREOCHROMIS NILOTICUS): The Effect Of Additioning Different Amount Of Weight Of Zeolite Stones On Transportation Of Tila Fish Seeds (Oreochromis niloticus) - Akbar, Muhammad; Rahmawati, Aryani; Kalih, L.A.T.T.W. Sukmaring; Atmanegara, Febrian Kusuma (Al-Qalbu: Jurnal Pendidikan, Sosial dan Sains, 2024)
This research aims to determine the effect of adding different weights of zeolite stone on the survival rate of tilapia (Oreocrhomis niloticus) seeds during the transportation process carried out at BBI Batu Kumbung, Lingsar District, West Lombok Regency. The method used in this research is an experimental method. The data analysis used was Analytical Analysis (ANASRA) at a real level of 5% and 1% to determine the percentage of mortality of the object under study. The results of this research were the use of zeolite stones with different weights for transporting tilapia (Oreocrhomis niloticus) seeds. The results of observations in treatment X0 using zeolite stone weighing 10 g mean percentage of life 74.66%, X1 treatment uses zeolite stone weighing 20 grams with an average survival percentage of 77.33%, X2 treatment uses zeolite stone weighing 30 g with an average survival percentage of 82.66%, and treatment X3 using zeolite stone weighing 40 g with an average survival percentage of 88.66%. ased on the Variety Scan analysis, it shows where F Calculated < F Table 5%, so it can be concluded that H0 is accepted or H1 is rejected, meaning that the difference in the weight of the zeolite stone does not have a significant effect on the survival rate of tilapia (Oreochromis Niloticus)